THE COMPARATIVE STUDY OF CHILD DRUG ABUSE CASES - Ibnu Taqwim; Pagar Hasibuan; Zulkarnain Zulkarnain (Jurnal Pembaharuan Hukum, 2021)
The inconsistency of law enforcement in implementing the substance of the narcotics law has led to a polemic in the community, especially against cases of drug abuse committed by minors, it becomes unclear, the approach method used in this study uses a normative juridical approach. The research found that children as perpetrators of narcotics crimes, if they are not proven to be dealers, which can be dangerous as a basis for imprisonment for children, it is necessary to be rehabilitated as regulated in the narcotics law. Considering that children who are perpetrators of narcotics crimes are only users and are affected by bad environmental conditions both in the family and the environment. Narcotics in the Islamic perspective is analogous to the prohibition of drinking alcohol. This prohibition is carried out because narcotics cause hatred, hostility, disaster and dangerous disasters, both for users, families, communities and the nation and state. Narcotics are prohibited in Islamic law and producers, dealers and users will be subject to Had or Ta’zir sanctions.